2018
DOI: 10.1093/jac/dky016
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tn916-like elements confer aminoglycoside/macrolide co-resistance in clinical isolates of Streptococcus gallolyticus ssp. gallolyticus

Abstract: Previously unknown Tn916-like mobile genetic elements conferring aminoglycoside/macrolide co-resistance make Sgg, collectively with other gut Firmicutes such as enterococci and eubacteria, a potential laterally active reservoir of these antibiotic resistance determinants among the mammalian gastrointestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Macrolide antibiotics are the oldest and most successful clinical ribosomal targeted antibiotics which target bacterial ribosomes to inhibit protein synthesis [43]. The macrolide antibiotics we detected were consistent with a study that proved clinical isolates of S. gallolyticus harbored macrolide [10]. Moreover, the speci c genes didn't play any role in the antibiotic resistance of S. gallolyticus strains (Fig.…”
Section: Identi Cation Of Virulence Factors For S Gallolyticus Strain...supporting
confidence: 86%
See 1 more Smart Citation
“…Macrolide antibiotics are the oldest and most successful clinical ribosomal targeted antibiotics which target bacterial ribosomes to inhibit protein synthesis [43]. The macrolide antibiotics we detected were consistent with a study that proved clinical isolates of S. gallolyticus harbored macrolide [10]. Moreover, the speci c genes didn't play any role in the antibiotic resistance of S. gallolyticus strains (Fig.…”
Section: Identi Cation Of Virulence Factors For S Gallolyticus Strain...supporting
confidence: 86%
“…These genes affect the host immune system and participate in adhesion to the lining of the cardiac epithelium, leading to infection and endocarditis [9]. Moreover, S. gallolyticus has been identi ed as a putative laterally active reservoir for these antibiotic resistance determining factors in the mammalian gastrointestinal microbiota, in particular, bacteria a liated to Firmicutes, such as Enterococci and Eubacteria [10]. For example, a previous study has reported that the S. gallolyticus subsp strains isolated from the samples of the clinical harbor a large number of antibiotic resistance genes that are susceptible to erythromycin and tetracycline [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent molecular characterization of 39 foodborne tetracycline-resistant isolates of S. bovis identified a novel mosaic tet (S/M) fusion [72]. Indeed, a new mechanism has been recently identified associated with macrolide resistance: two previously unknown conjugative transposons, Tn6263 and Tn6331, were found to confer aminoglycoside/macrolide co-resistance identified in a clinical isolate of SGSG responsible for infective endocarditis and colorectal cancer [73].…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…A better understanding of the dissemination mechanism of AR genes is essential for monitoring and controlling drug resistance. Previous studies have revealed that mobile genetic elements (MGEs) play significant roles in the horizontal transfer of AR genes in Streptococcus ( Puopolo et al, 2007 ; Chancey et al, 2015 ; Davies et al, 2015 ; Kambarev et al, 2018 ). Integrative conjugative elements (ICEs), prophages and tandem ICE-prophages located at different insertion sites were common MGEs described in S. suis ( Uruen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%